A simple method for estimating half-life of drugs obeying Michaelis-Menten elimination kinetics - DING Yong; HUANG Da-kuang; LUO Jian-ping (Acta Pharmacologica Sinica, 2016)
AIM: To establish a simple method for estimating half-life of drugs obeying Michaelis-Menten elimination kinetics. METHODS: A linear relationship is sketched between elimination half-life and drug concentration in blood that obey Michaelis-Menten elimination kinetics. A simple method is proposed to draw a regression line of blood drug concentration vs time after a single bolus intravenous injection. RESULTS & CONCLUSION: The elimination half-life can be read from the regression line. The method can also be used to estimate the time required for the plasma concentration of a drug to decrease any fraction.